KAJIAN YURIDIS PENGALIHAN PIUTANG DARI KREDITUR KEPADA PERUSAHAAN FACTORING DALAM PERUSAHAAN PEMBIAYAAN ANJAK PIUTANG - Pebria Satyani, Luh Kade; Dharma Kusuma, Anak Agung Gede Agung (Kertha Semaya : Journal Ilmu Hukum, 2014)
Factoring is a financing activity in the form of short-term trade receivables of a company following the administration of the receivables. Factoring agreement is an agreement underlying the displacement of a number of bills receivable to another party. Therefore, this paper will explain how the legal effect of the transfer of the receivables from the creditor to the factoring company. Besides, this paper also describes how the transfer from the creditor to the receivables factoring company without the knowledge of the debtor. So a debtor can only be bound if he had been aware of and approved the transfer of the receivables from the creditor to the factoring company. The method used in this paper is the normative method refers to the sources of law.
Keywords: Agreement, Factoring, Due Law, Transfer